2001
DOI: 10.1108/07363760110365813
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing cross‐cultural differences in consumer complaint behavior and intentions: an empirical examination

Abstract: Understanding consumer dissatisfaction and its outcomes, a focus of consumer complaint behavior (CCB) research, has become a critical factor for business firms pursuing market penetration strategies where selling more to existing customers oftentimes is the key to profitability. However, CCB research to date has been primarily western in its orientation. This begs questions as to the extent to which western corporations can rely on its findings in markets with non‐western cultures. Based on an empirical invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(242 citation statements)
references
References 52 publications
7
218
3
6
Order By: Relevance
“…Finally, the findings showed that the probability to complain is controlled by gender as male complainers are more likely to show their dissatisfaction as compared to the female complainers supporting the previous works of Sujithamrak & Lam, 2005;Au, Hui, & Leung, 2001;Liu & McClure , 2007. Marketing literature has established the fact that consumer characteristics are important factors in studying customer behaviour (Singh, 1990).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Finally, the findings showed that the probability to complain is controlled by gender as male complainers are more likely to show their dissatisfaction as compared to the female complainers supporting the previous works of Sujithamrak & Lam, 2005;Au, Hui, & Leung, 2001;Liu & McClure , 2007. Marketing literature has established the fact that consumer characteristics are important factors in studying customer behaviour (Singh, 1990).…”
Section: Discussionsupporting
confidence: 76%
“…These characteristics include cultural, education, age, income, gender (Sujithamrak & Lam, 2005;An, Hui, & Leung, 2001;Liu & McClure , 2007). However, earlier literature on CCB supported the notion that demographics variables have been found to be the antecedents of CCB ( Jacoby & Jaccard, 1981;Bearden & Oliver, 1985;Richins,1987;Singh, 1990).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Previous studies confirmed that dissatisfaction is the main reason for complaints (Liu & McClure, 2001;Williams, Drake, & Moran, 1993). This view has its roots in expectancy disconfirmation theory (Oliver, 1989), which suggests that dissatisfaction results from a discrepancy between customer expectation and perceived product/service performance.…”
Section: Customer Satisfaction/dissatisfaction and Complaining Behaviorsupporting
confidence: 50%
“…The reason for naming the group is based on the keywords used in the items such as "discuss," "request," and "inform" for Soft Public Complaint and "write," "report," "complain," and "take legal action" which is more stern. In previous studies, using items CCB1, CCB2 and CCB3 for public action Liu, Watkins and Youjae (1997), Singh (1988), Liu and McClure (2001) named it as "Voice Responses" whereas items CCB4, CCB5, CCB6 and CCB7 as third party responses. On the other hand, Ndubisi and Ling (2006), Malhotra et al (2008) and Kitapci and Dortyol (2009) lumped all items into public complaint.…”
Section: Preliminary Analysismentioning
confidence: 99%
“…In this case, the consumers dealt with the service provider or the organization to inform, discuss or request something with regard to their dissatisfaction. Items for this construct were taken from Liu and McClure (2001), Ndubisi and Ling (2006), and Malhotra et al (2008). Seven items were used to measure soft public action on a five-point scale ranging from 1 (Strongly Disagree) to 5 (Strongly Agree).…”
Section: Public Actionmentioning
confidence: 99%